THEORETICAL AND EXPERIMENTAL INVESTIGATIONS OF SOLID FUEL-RICH PROPELLANT FOR RAM ROCKET APPLICATIONS (Journal of Engineering, 2005)
Five formulations of fuel-rich propellant consisting hydroxy-terminated poly-butadiene (HTPB) based polymer, ammonium perchlorate (AP) and magnesium (Mg) or aluminum (Al) as additive have been processed and investigated. Theoretical calculations of flame temperature and gas composition were determined by NASA-273 computer code. The sustained ignition/ combustion of such propellant is possible with long duration pyrotechnic igniters. The experimental investigations of the effect of solid particle size range and content on fuel ballistic and mechanical properties have revealed that a considerable enhancement may be obtained with fine particle size and high content percent. High air-to-fuel ratio increases the combustion efficiency in the ramjet-mode resulting in higher specific impulse.